2022
DOI: 10.3389/fpubh.2022.1009703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on the proportion of physically active children and adults worldwide: A systematic review and meta-analysis

Abstract: IntroductionSafety measures implemented to address the COVID-19 pandemic have had a profound impact on the mobility of people worldwide We synthesized the global evidence on physical activity (PA) participation before and during the pandemic.MethodsWe conducted a systematic review, searching PubMed, Embase, WHO Global literature on coronavirus disease (between January 2020 and April 2022), and reference lists. Meta-analysis and meta-regression were conducted to quantitatively synthesize the data.Results and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…With the closure of sports facilities and the inability to perform their favorite physical activities, such as team games, gym workouts, and swimming, some of the respondents began to train at home and in outdoor settings [83] in an attempt to stay motivated to practice sports [84]. Unfortunately, significant decreases in physical activity have been recorded in most countries [85], which was also confirmed in the present study. In Polish women, the percentage of physically inactive respondents in 2021 increased by as much as about 400% compared to 2019 (from 5.42% in 2019 to 16.54% in 2021), while the fraction of those regularly active decreased from 69.48% to 42.48%.…”
Section: Covid-19supporting
confidence: 78%
“…With the closure of sports facilities and the inability to perform their favorite physical activities, such as team games, gym workouts, and swimming, some of the respondents began to train at home and in outdoor settings [83] in an attempt to stay motivated to practice sports [84]. Unfortunately, significant decreases in physical activity have been recorded in most countries [85], which was also confirmed in the present study. In Polish women, the percentage of physically inactive respondents in 2021 increased by as much as about 400% compared to 2019 (from 5.42% in 2019 to 16.54% in 2021), while the fraction of those regularly active decreased from 69.48% to 42.48%.…”
Section: Covid-19supporting
confidence: 78%
“…Additional file 12 [ 54 , 67 , 77 , 139 , 153 ] summarizes single-arm evidence about events caused by the COVID-19 vaccine. Additional file 13 [ 49 , 50 , 58 , 82 , 99 , 113 , 142 ] summarizes single-arm evidence about health impacts during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study suggested that increased social isolation during the pandemic had a negative impact on physical activity levels, leading to increased sedentary behavior and affecting sleep duration and quality (Luciano et al, 2021). A meta‐analysis conducted by Chaabna and colleagues found that the prevalence of physical activity decreased during the pandemic compared to pre‐pandemic period (Chaabna et al, 2022). Additionally, studies have indicated that increased screen time was associated with poorer sleep quality (Gupta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%